2022
DOI: 10.7554/elife.78984
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of condensin II-mediated chromosome assembly using in vitro assays

Abstract: In vertebrates, condensin I and condensin II cooperate to assemble rod-shaped chromosomes during mitosis. Although the mechanism of action and regulation of condensin I have been studied extensively, our corresponding knowledge of condensin II remains very limited. By introducing recombinant condensin II complexes into Xenopus egg extracts, we dissect the roles of its individual subunits in chromosome assembly. We find that one of two HEAT subunits, CAP-D3, plays a crucial role in condensin II-mediated assembl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 51 publications
4
32
0
Order By: Relevance
“…We have constructed and tested a panel of mutant complexes to provide evidence that the N-tail of the kleisin subunit CAP-H negatively regulates the loading of condensin I and the resultant assembly of mitotic chromosomes in Xenopus egg extracts ( Figure 5A ). Recent studies from our laboratory showed that deletion of the CAP-D2 C-tail, which also contains multiple SP/TP sites ( Figure 2—figure supplement 1A ), has little impact on condensin I function as judged by the same and related add-back assays using Xenopus egg extracts ( Kinoshita et al, 2022 ; Yoshida et al, 2022 ). Thus, the CAP-H N-tail represents the first example of negative regulatory elements that have been identified in vertebrate condensin I. Phosphorylation-deficient mutations (H-N19A) and phosphorylation-mimetic mutations (H-N19D) in the N-tail decelerate and accelerate condensin I loading, respectively, allowing us to propose the following working model ( Figure 5B ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have constructed and tested a panel of mutant complexes to provide evidence that the N-tail of the kleisin subunit CAP-H negatively regulates the loading of condensin I and the resultant assembly of mitotic chromosomes in Xenopus egg extracts ( Figure 5A ). Recent studies from our laboratory showed that deletion of the CAP-D2 C-tail, which also contains multiple SP/TP sites ( Figure 2—figure supplement 1A ), has little impact on condensin I function as judged by the same and related add-back assays using Xenopus egg extracts ( Kinoshita et al, 2022 ; Yoshida et al, 2022 ). Thus, the CAP-H N-tail represents the first example of negative regulatory elements that have been identified in vertebrate condensin I. Phosphorylation-deficient mutations (H-N19A) and phosphorylation-mimetic mutations (H-N19D) in the N-tail decelerate and accelerate condensin I loading, respectively, allowing us to propose the following working model ( Figure 5B ).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the negative regulation by the kleisin N-tail reported here is not shared by condensin II. Interestingly, however, a recent study from our laboratory has shown that the deletion of the CAP-D3 C-tail causes accelerated loading of condensin II onto chromatin ( Yoshida et al, 2022 ). It is therefore possible that condensins I and II utilize similar IDR-mediated regulatory mechanisms, but they do so in different ways.…”
Section: Discussionmentioning
confidence: 96%
“…provided evidence that the N-tail of the kleisin subunit CAP-H negatively regulates the loading of condensin I and the resultant assembly of mitotic chromosomes in Xenopus egg extracts(Fig 5A). Recent studies from our laboratory showed that deletion of the CAP-D2 C-tail, which also contains multiple SP/TP sites (Fig EV3A), has little impact on condensin I function as judged by the same and related add-back assays using Xenopus egg extracts(Kinoshita et al, 2022;Yoshida et al, 2022). Thus, the CAP-H Ntail represents the first example of negative regulatory elements that have been identified in vertebrate condensin I. Phosphorylation-deficient mutations (H-N19A) and phosphorylation-mimetic mutations (H-N19D) in the N-tail decelerate and accelerate condensin I loading, respectively, allowing us to propose the following working model(Fig 5B).…”
mentioning
confidence: 94%
“…The Hirano lab recently demonstrated that, for the Xenopus system, in addition to core histones and histone chaperones, purified Topoisomerase IIa and condensin I are sufficient to reconstitute mitotic chromosomes in vitro [ 48 ]. Condensin II was not tested in this initial study, but a more recent study from the Hirano lab shows that in more complex Xenopus egg extracts condensin II can generate compact chromosomes without condensin I [ 49 ]. Other studies, in chicken and mammalian cells, have shown that compacted rod-shaped chromosomes, somewhat resembling mitotic chromosomes, can be generated when only condensin I, or only condensin II is present, although the morphologies of the chromosomes clearly differ from wild type chromosomes pointing to the presence of folding defects [ 19 , 36 , 50 ].…”
Section: From the Chromosome Scaffold To Mitotic Chromosome Folding M...mentioning
confidence: 99%